Pemodelan Degradasi dan Agradasi Dasar Sungai dengan Beberapa Persamaan di Sungai Winongo Yogyakarta - Harsanto, Puji; Sutri, Galuh Nanda; Rahadiansyah, Shakti; Lesmana, Surya Budi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
Calculating riverbed degradation and aggradation is essential in designing riverbank protection structures, particularly for determining foundation depth. Excessive degradation can compromise foundation stability, significantly increasing the risk of structural failure. Numerous predictive models for egradation and aggradation have been developed by researchers, highlighting the importance of selecting an equation that closely aligns with the specific characteristics of the river to achieve optimal design accuracy. This study aims to determine the most suitable predictive model for riverbed degradation and aggradation. A case study was conducted along a 43.75 km of the Winongo River Yogyakarta. The simulation involved riverbed sediment data collected at 500 m intervals from upstream to downstream, and secondary discharge data comprising average daily discharge for both wet and dry months. The selected grainsize parameter follows standards in HEC-RAS 6.3.1, with the Meyer Peter Müller equation applied to d90, Engelund Hansen to d50, and Laursen Copeland to d84. Simulation results of riverbed degradation were then compared against observed conditions of riverbank erosion. Riverbank steepness or protective structure failure indicates excessive riverbed degradation, while stable conditions suggest otherwise. Based on the simulations conducted on the Winongo River, the Engelund Hansen equation provided average degradation estimates more consistent with field conditions than the other two equations.Keywords: degradation and agradation, transport sediment equations, HEC-RAS, river bank